The invasive, non-native slipper limpet Crepidula fornicata is poorly adapted to sediment burial. (May 2018) - Powell-Jennings, Chloe; Callaway, Ruth
Abstract: The American slipper limpet Crepidula fornicata is an invasive, non-native species (INNS) abundant along the European coast. Its further distribution may be facilitated by activities such as dredging and spoil disposal, and the aim of this study was to assess whether C . fornicata is able to survive sediment burial. The slipper limpet was found attached to hard substratum in intertidal areas, but it was absent at a nearby subtidal dredge spoil site. In laboratory experiments 22% of C . fornicata emerged when buried under a 2 cm sediment-layer; only half of them survived. When buried under ≥6 cm none re-surfaced or survived. The results provided evidence that C . fornicata is poorly adapted to adjust its vertical position in sediment and is killed by sudden burial underneath 2 to 6 cm of sediment. The combined laboratory experiments and field surveys suggested that C . fornicata has limited scope to survive the dredge spoil disposal process. Graphical abstract: Highlights: The most important factor determining mortality in buried Crepidula fornicata was the thickness of the sediment layer. The invasive non-native slipper limpet C . fornicata died when buried under ≥6 cm of sediment. Duration, shell size or whether the species occurred in stacks or as individuals was not significant. C . fornicata was able to emerge from shallow, 2 cm burial after 7 days. C . fornicata was not found at a dredge spoils disposal site.